How do employees currently admitted to acute psychiatric inpatient units rate their psychosocial working conditions with the COPSOQ (Copenhagen Psychosocial Questionnaire). (June 2023) - Brucks, Adele; Lang, Anne; Blank, Daniela; Lincke, Hans-Joachim; Riedl, Lina; Siafis, Spyridon; Brieger, Peter; Hamann, Johannes
Background: In recent years it could be shown that psychosocial working conditions and mental health of employees are closely correlated. One well-established instrument to measure psychosocial stress at work is the COPSOQ (Copenhagen Psychosocial Questionnaire, German Standard Version). It is an 84 item self-rating instrument addressing several domains of psychosocial working conditions and is generally used for risk assessments in companies. Aims: To examine associations between COPSOQ ratings with clinical features and symptoms of employees who currently suffer from an episode of a mental illness requiring inpatient treatment. Method: For 265 inpatients with mental disorders who participated in a cluster randomized trial (RETURN-study) COPSOQ-data were available as part of the baseline data acquisition. These data were compared with the German COPSOQ validation sample of the Freiburg research center for occupational sciences (FFAW; approximately 250, 000 participants). For subdomains of the COPSOQ that showed major and significant differences between the two samples regression analyses were done to predict COPSOQ scores within the RETURN-sample. Results: Psychiatric inpatients did not assess their working conditions significantly different compared to the population based FFAW sample. However, with regard to the effects of working conditions (general health, burnout, presenteeism, and intention to leave the job) there were major differences between the two samples with the clinical sample expressing more negative views. In the RETURN sample these were predicted by a greater expression of depressive symptoms. Conclusions: The linkage between work and mental wellbeing is complex. Mental illness is not necessarily a result of poor working conditions, while good working conditions may not in every case prevent symptoms of bad health, even if such associations exist.